PEMBERSIHAN LANTAI KAMAR OPERASI ZONA 4 TERHADAP JUMLAH KOLONI BAKTERI - joko pitoyo (Poltekkes Kemenkes Malang, 2018)
The operating room is the most privileged room in the hospital with the most special management compared , because this room is used for elective and acute surgery that requires high levels of sterilitation. The purpose of this research is to know the effectiveness of cleaning of operating room floor of zone 4 on the number of bacterial colonies in Central Surgery Installation (IBS) Ngudi Waluyo Wlingi Hospital. The research design used in this research is Cross Sectional Analytical Observation. Samples from this study are the contaminated clean room operating floors and the dirty operating room floors taken with swabs of the floor at 3 rounds . The results of this study indicate that the clearance of the operating room zone 4 50% in accordance with existing cleaning procedures and there are differences in the number of colonies of bacteria before and after done cleaning room floor 4 zone operation in round 1, round 2 and round 3 in the Contaminated Clean Operating Room and Gross Operation Room. The results of statistical tests show that p value is 0.004, meaning that there is effectivity of cleaning of floor of zone 4 operating room to number of bacterial colonies in floor. The recommendation of this research is the need for recleaning zona 4 room operation before activity especially the floor to suppress the number of bacterial numbers Keywords : Floor cleaning Operating room , Number of bacterial colonies